Factors Influencing Hotels’ Online Prices - Moro, Sérgio (2018)
Moro, S., Rita, P., & Oliveira, C. (2018). Factors Influencing Hotels’ Online Prices. Journal of Hospitality Marketing and Management, 27(4), 443-464. DOI: 10.1080/19368623.2018.1395379